The politics of human rights a global perspective - Evans, Tony (Pluto Press, 2005)
Tony Evans argues that the state's central role in protecting and promoting rights has been severely weakened under the pressure of globalisation and that as a consequence human rights are increasingly under threat.
Keywords: Globalisierung; Menschenrecht; Globalization; Human rights; Menschenrechtspolitik